An assessment of an urban protected area through a space syntax approach: the case of Ordu, Turkiye - Karabork, Rabia Nurefsan; Yesil, Pervin; Yesil, Murat (Journal of Environmental Engineering and Landscape Management, 2025)
Traditional architecture, preserved and integrated into urban life, has the potential to become a point of attraction for cities and contribute to their image. The aim of this study is to analyse the configurational characteristics of the urban conservation area and its immediate surroundings, which constitute the historical core of the city of Ordu, and the general condition of the registered architectural examples in the area. The evaluations of the spatial configuration are based on the analyses of connectivity, global and local integration, which are the basic parameters of the spatial sequence method. As a result of the study, it can be seen that the two main traffic arteries of the area, Sıtkı Can Street and Dr Osman Hilmi Memecan Street, have the highest sequence values. Although it can be seen that Sıtkı Can Street, one of these traffic arteries, is more advantageous than other streets in terms of the registered civil architecture stock in the area, it is important that restoration processes should be implemented as soon as possible in order to ensure structural and historical continuity and not to lose the registered civil architecture examples located in different parts of the study area.